Peran Kemajuan Teknologi Informasi dalam Memoderasi Pengaruh Motivasi Investasi, Pengetahuan Investasi,,Pelatihan Pasar Modal, , Modal Investasi Minimal dan Persepsi Resiko terhadap Minat Investasi Generasi Milenial di Pasar Modal - Raflis, Ratnawati; Thahirah, Khadijah Ath; ., Rahmaita; ., Indrayeni (CV. ITTC INDONESIA, 2024)
Technology is an instrument that has an impact on the business sector, especially the capital market. Cost efficiency will be achieved through the use of technology. Apart from that, the speed and accuracy obtained from the use of technology are what is needed for trading on the stock exchange floor so that investors, brokers and related institutions can quickly analyze and make investment decisions. Furthermore, the capital market sector, in which thousands of companies are registered, actively buying and selling their shares, is very dependent on speed and accuracy in carrying out transactions on the stock exchange floor. The solution for this is that the existence of technology is really needed so that investors, brokers, traders and related institutions can make accurate decisions.The convenience of the existence of this technology is one of the factors that triggers the interest of the millennial generation, especially students, to invest, especially the convenience for novice investors who have just started investing and who do not yet have their own income.Furthermore, other factors that are thought to influence investment interest are Investment Motivation, investment knowledge, capital market training, Minimum Investment Capital and Risk Perception, all of which are Independent variables and Information Technology is presented as a moderating variable in order to strengthen the relationship between the aforementioned Independent variables and Investment Interest. .The data collection method used questionnaire and documentation techniques and the sampling technique used was purposive sampling for students from the Faculty of Economics and Business at three universities in the city of Padang. The data analysis method uses multiple linear regression tests and Moderated Linear Regression (MRA).The research results conclude that the findings from the answer to the problem formulation are that the Moderating Variable of Technological Progress on Investment Motivation has a significance value of 0.032. This means that the significance value is 0.032<0.05. So, it can be seen that the variable Moderation of Technological Progress on Investment Motivation has a significant effect on investment interest.